Multifunctional flame-retardant phase change film based on PEG, LDH and CF as well as preparation method and application of multifunctional flame-retardant phase change film

By using the multifunctional flame-retardant phase change film preparation method of PEG, LDH and CF in composite phase change materials, the problem of incompatibility of composite phase change materials is solved, and the thermal runaway of high-energy-density batteries and high-power electronic equipment is effectively suppressed, and the photothermal energy storage function is equipped.

CN119505374AActive Publication Date: 2025-02-25ZHONGBEI UNIV

Patent Information

Application Number
CN202411563441.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-25
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Existing composite phase change materials are incompatible with thermal management, flame retardant and electromagnetic shielding, making it difficult to effectively suppress the thermal runaway problem of high-energy-density batteries and high-power electronic devices.

Method used

A multifunctional flame retardant phase change film preparation method based on PEG, LDH and CF was used to prepare a flame retardant phase change film with electromagnetic shielding and thermal management performance by a combination of CF carbon foam framework, polyethylene glycol phase change material and layered bimetal hydroxide LDH.

Benefits of technology

It realizes compatibility of composite materials in thermal management, flame retardant and electromagnetic shielding, delays the thermal runaway of the battery, and has the functions of photothermal energy storage and thermal runaway suppression.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505374A_ABST
    Figure CN119505374A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of design synthesis and thermal runaway inhibition of composite phase-change materials, and provides a preparation method and application of a multifunctional flame-retardant phase-change film based on PEG, LDH and CF in order to solve the problem that photo-thermal energy storage and thermal runaway inhibition of existing composite phase-change materials cannot be compatible, and the flame-retardant phase-change film has photo-thermal energy storage and thermal runaway performance. A CF carbon foam skeleton is used as a matrix, a shape skeleton and a light absorption and heat conduction material, polyethylene glycol is used as a phase change material, a flame retardant layered double hydroxide LDH is added for full mixing and hybridization, and the multifunctional flame-retardant phase change film is obtained by using a fusion film laying method. The composite film prepared by the invention combines excellent shape stability, photo-thermal energy storage capability and efficient thermal runaway inhibition capability, so that the composite film has wide application prospects in the fields of heat energy storage, battery thermal runaway inhibition, microelectronic packaging, intelligent buildings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite phase change material design, synthesis and thermal runaway suppression, and specifically relates to a method for preparing a multifunctional flame-retardant phase change film based on PEG, LDH and CF and an application thereof, wherein the flame-retardant phase change film has photothermal energy storage and thermal runaway suppression performance. Background Art

[0002] In daily life, a large number of high-energy-density batteries and high-power electronic devices have appeared. The popularity of high-energy-density batteries and high-power electronic devices has brought about serious problems of thermal runaway, which may not only lead to a decline in device performance, but also cause equipment damage and even safety hazards. Therefore, there is an urgent need to develop advanced thermal management technologies to effectively control and disperse the heat generated by the equipment to ensure the stability and safety of equipment operation. Similar to the solution to the problem of electromagnetic radiation, we now need to focus on solving these challenges and develop innovative electronic packaging materials that can integrate the ability to suppress thermal runaway of high-energy-density batteries and high-power electronic devices. Materials with thermal runaway suppression functions often need to have flame retardant and thermal management functions.

[0003] Traditional flame retardants have many obvious shortcomings, such as large effective addition amount or need to be compounded with other flame retardants to effectively retard flames, and even pyrolysis or combustion will produce toxic substances. Therefore, it is very necessary to find an environmentally friendly, non-toxic, low-volume and high-efficiency flame retardant. Layered double hydroxide (LDH) is green, environmentally friendly, non-toxic, and has a large specific surface area. It can absorb the smoke generated during combustion. When pyrolysis occurs, it will take away huge heat and release non-combustible gases such as water vapor. The metal oxides after combustion will form a dense film to isolate the air. In addition, due to the special layered structure of LDH itself and its large specific surface area, LDH has strong adsorption properties and has long been used to load drugs in medicine.

[0004] Solid-liquid organic phase change materials (PCMs) are ideal candidates for thermal management materials, with excellent properties such as suitable phase change temperature, strong chemical stability, non-toxicity, low corrosion, low cost and easy access, and negligible supercooling. Nevertheless, the leakage of liquid phase change materials during solid-liquid phase change and low thermal conductivity are two long-standing and urgent problems that need to be solved, which makes their application very difficult. If these two problems cannot be effectively solved, the leakage of liquid PCM will reduce the absolute content of PCM, and the leaked liquid PCM will affect the working environment; insufficient thermal conductivity will reduce the charging and discharging speed of electronic devices. There are currently two main methods to solve these two problems: adding different additives to prepare high thermal conductivity phase change composite materials and using shape skeletons or shape stabilization technology to fix PCM. Among them, the skeleton can not only effectively solve the PCM leakage problem, but also enrich the performance of the composite material. This method can also process the PCM composite material into the required shape.

[0005] Photothermal energy storage is a technology that uses solar energy to convert it into storable thermal energy, which has broad application prospects. In the past few decades, scientists have been working hard to find materials that can efficiently absorb solar energy and convert it into thermal energy. First of all, porous carbon materials have excellent light absorption properties, which can efficiently absorb sunlight and convert it into thermal energy. This provides a feasible way to use solar energy for thermal power generation. At the same time, porous carbon materials also exhibit good thermal conductivity and can effectively conduct and store absorbed thermal energy. This makes it an ideal thermal energy storage material that can release stored thermal energy when needed to meet energy needs. Summary of the invention

[0006] In order to solve the problem that thermal management, flame retardancy and electromagnetic shielding of current composite phase change materials are incompatible, the present invention provides a method for preparing a multifunctional flame retardant phase change film based on PEG, LDH and CF and its application, wherein the flame retardant phase change film has electromagnetic shielding and thermal management properties.

[0007] The present invention is achieved by the following technical scheme: a multifunctional flame-retardant phase-change membrane based on PEG, LDH and CF, with CF carbon foam skeleton as the matrix and as the shape skeleton, light-absorbing and heat-conducting material, polyethylene glycol as the phase-change material, and then adding flame retardant layered double metal hydroxide LDH to fully mix and hybridize, and using the melt-laying method to obtain the multifunctional flame-retardant phase-change membrane; wherein: the mass ratio of the phase-change material, the skeleton and the flame retardant is: 7-8:1-1.5:1-1.5.

[0008] The phase change material can also be decanoic acid or octadecane to replace polyethylene glycol; the skeleton can be polypyrrole tube PPY or carbonized gelatin to replace CF.

[0009] The method for preparing the multifunctional flame-retardant phase change film based on PEG, LDH and CF comprises the following specific steps: (1) Preparation of CF skeleton: 0.5g agar powder and 2g sodium chloride were dissolved in 20mL deionized water, and the mixed solution was heated to 90℃ and stirred continuously. During this process, the water in the mixed solution evaporated continuously. After a certain period of time, the mixed solution formed a uniform hydrosol; after cooling to room temperature, the formed hydrosol was freeze-dried in a -50℃ vacuum freeze dryer for 72h to obtain a white solid product; the white solid product was placed in a tubular furnace, and the heating rate was controlled at 10℃ / min under an argon atmosphere, and the temperature was raised to 700℃ for 2h. The pyrolysis temperature zone was far lower than the melting point of NaCl (801℃) to prevent the melting of NaCl crystals. After cooling to room temperature, the product was soaked in water overnight to dissolve NaCl, and then filtered and washed. The resulting filter cake was dried in an oven at 80℃ to obtain nanoporous carbon foam (CF); (2) Preparation of CF@Mg Al-LDH composite material: Weigh 0.5 g of CF powder, 1.62 g of MgCl 2 6H 2 O, 0.9 g AlCl 3 ·H 2 O and 2.4 g of urea were placed in a high-pressure reactor and mixed evenly. The reactor was placed in an oven at 100 °C for hydrothermal reaction for 12 h. After cooling to room temperature, the product was taken out and centrifuged and washed three times, and then placed in an oven at 80 °C to dry to obtain CF@MgAl-LDH. (3) Preparation of composite membrane: Weigh 0.5 g CF powder, 25 g cellulose, and 4 g PEG and mix them in 100 ml deionized water. Stir at 600 r / min for 6 h to obtain a uniform mixture. Pour the mixture into a cylindrical mold with a radius of 15 mm and a height of 20 mm. Place the mold in a vacuum oven at 80 °C and bake for 24 h. In other words, the CF / PEG film is obtained by the melt casting method.

[0010] 0.5 g of CF powder was replaced with 0.5 g of CF@MgAl-LDH powder, and the other materials were the same as in the steps to obtain CF@LDH / PEG film.

[0011] The multifunctional flame-retardant phase-change film is solid powder or block.

[0012] The application of the multifunctional flame-retardant phase-change film based on PEG, LDH and CF or the multifunctional flame-retardant phase-change film based on PEG, LDH and CF prepared by the method in delaying thermal runaway of batteries is specifically as follows: the composite film is coated on the battery and placed in the insulated cavity of an adiabatic accelerating calorimeter, and the temperature change is monitored by a thermocouple temperature measuring device, and the real-time temperature, temperature difference and maximum temperature rise rate under different working environments are obtained to characterize the performance of delaying thermal runaway. The composite nanofibers are placed under a sunlight simulation lamp for irradiation, and their temperature changes are monitored, and their photothermal conversion capacity is determined according to the real-time temperature, sample specific heat and light power within a certain period of time.

[0013] The phase change material prepared by the present invention is not limited to a film, but can also be a solid powder or a block, and has both the functions of photothermal energy storage and thermal runaway suppression.

[0014] The packaging material of the battery is any one of aluminum alloy, copper or iron, and the heat sink is foamed nickel or foamed copper or any metal.

[0015] Application of the multifunctional flame-retardant phase-change film based on PEG, LDH and CF or the multifunctional flame-retardant phase-change film based on PEG, LDH and CF prepared by the method in photothermal energy storage materials, microelectronic packaging materials or intelligent building materials.

[0016] In order to obtain a porous carbon material suitable for loading a phase change material, the present invention uses easily available NaCl and agar, uses an auxiliary pyrolysis method to prepare a porous carbon foam material CF, and grows Mg Al-LDH with a flame retardant effect in situ on the CF porous skeleton by a hydrothermal synthesis method. The unique porous structure and high specific surface area of ​​CF enable the phase change material PEG to rely on capillary effect and surface tension after the solid-liquid phase change so that the liquid phase PEG will not leak. The phase change composite material formed by CF and PEG has excellent photothermal energy storage capacity and thermal management performance due to the high energy storage density of PEG and the high thermal conductivity, good absorbance and good shape stability of CF as a carbon material. The presence of Mg Al-LDH gives the composite phase change material a certain flame retardant ability. After the composite material is made into a flexible film by a vacuum melt film laying method, it still has the above-mentioned properties and its application scenarios are further expanded. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the synthetic route diagram of Example 1; Figure 2SEM and TEM images of the samples; in the figure: (a-a') is the (a-a') SEM image of CF; (b-b') is the SEM image of CF@LDH; (c-c') is the SEM image CF / PEG; (d-d') is the SEM image of CF@LDH / PEG; (e) is the local surface SEM image of CF / PEG, and the corresponding EDS elemental maps of C, O, Mg and Al; (f) is the local surface SEM image of CF @ LDH / PEG, and the corresponding EDS elemental maps of C, O, Mg and Al; Figure 3 XRD and FTIR graphs of the samples; in the figure: a is the XRD curves of Mg Al-LDH, PEG, CFLDH, CF / PEG and CF@LDH / PEG; b is the FT-IR spectra of CF, PEG, CF@LDH, CF / PEG and CF@LDH / PEG; Figure 4 DSC and TGA graphs of the samples; in the figure: a is the DSC curve of PEG, CF / PEG and CF@LDH / PEG; b is the TGA curve of CF, CF@LDH, CF / PEG and CF@LDH / PEG; Figure 5 is the thermal conductivity of the sample; Figure 6 This is the infrared thermal image of the sample; Figure 7 Graphs of sample absorbance and photothermal conversion temperature; in the figure: a is a diagram of a photothermal conversion device; b is an absorbance diagram of PEG and a composite material; c is a graph of photothermal conversion temperature of PEG and a composite material; Figure 8 The bending and tensile test diagram of CF@LDH / PEG; Fig. 9 The temperature change diagram of the adiabatic accelerated calorimetry experiment of 18650 lithium-ion batteries wrapped and not wrapped by CF@LDH / PEG at 100% SOC state. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0020] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.

[0021] The experimental methods in the following examples are conventional methods unless otherwise specified. The instruments and equipment used in the following examples are conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.

[0022] 1. Experimental materials: Agar, sodium chloride, PEG, magnesium chloride hexahydrate, aluminum chloride hexahydrate, urea, cellulose PEG-8000 (Mn = 8000 g / mol, 99%), urea (AR), AlCl3·H2O (AR, 97%), MgCl2·6H2O (AR), agar (BR), sodium chloride (AR, 99%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Cellulose (2%) was purchased from Guilin Qihong Technology Co., Ltd. All drugs did not require further purification.

[0023] 2. Preparation method of CF: Agar powder (0.5 g) and salt (sodium chloride, NaCl; 2 g) were dissolved in deionized water (20 mL) and stirred continuously at 90°C to form a uniform hydrosol. After cooling to room temperature, the formed hydrosol was freeze-dried in a -75°C vacuum freeze dryer for 72 h to obtain a white solid product. The white solid product was placed in a tube furnace and heated at 700°C in an argon atmosphere (heating rate 10°C min-1) for 2 h. The pyrolysis temperature zone was far below the melting point of NaCl (801°C) to prevent the melting of NaCl crystals. After cooling to room temperature, the product was soaked in water overnight to dissolve NaCl, then filtered and washed, and the resulting filter cake was dried in an oven at 80°C to obtain nanoporous carbon foam (CF).

[0024] Preparation of CF@LDH composite: 0.5 g of CF powder, 1.62 g of MgCl2·6H2O, 0.9 g of AlCl3·H2O and 2.4 g of urea were weighed and put into a high-pressure reactor. After mixing evenly, the reactor was placed in an oven at 100°C for hydrothermal reaction for 12 hours. After cooling to room temperature, the product was taken out and centrifuged and washed 3 times, and then placed in an oven at 80°C to dry to obtain CF@MgAl-LDH.

[0025] MgAl-LDH was prepared separately using the same procedure as the CF@MgAl-LDH composite without adding CF powder.

[0026] The specific preparation example of the multifunctional flame-retardant phase change membrane CF@LDH / PEG based on PEG, LDH and CF is as follows: Example 1: Preparation of CF@LDH / PEG composite membrane material: Weigh 0.5g CF@MgAl-LDH powder, 25g cellulose, and 4g PEG and mix them in 100ml deionized water. Stir at 600r / min for 6h to obtain a uniform mixture, pour it into a cylindrical mold with a radius of 15mm and a height of 20mm, place the mold in a vacuum oven at 80℃ and bake for 24h. That is, the CF@LDH / PEG film is obtained by the vacuum melt coating method.

[0027] The CF@LDH / PEG composite membrane was prepared by vacuum melt casting method. Figure 1 To avoid low-temperature crystallization of PEG, the mixture was placed in a vacuum drying oven and kept at 80°C for 12 h. The mixed solution of CF@LDH / PEG composite membrane was vacuum melt-cast.

[0028] Application of the obtained CF@LDH / PEG double-layer film composite material: The composite film is coated on the battery and placed in the insulated cavity of the adiabatic accelerating calorimeter. The temperature change is monitored by a thermocouple temperature measuring device, and the real-time temperature, temperature difference and maximum temperature rise rate under different working environments are obtained to characterize the thermal runaway delay performance. The composite nanofiber is placed under a sunlight simulation lamp for irradiation, and its temperature change is monitored. Its photothermal conversion capacity is determined based on the real-time temperature, sample specific heat and light power within a certain period of time.

[0029] Example 2: Preparation of CF / PEG: 0.5 g of CF@LDH in Example 1 was replaced with 0.5 g of CF, and the rest of the method was the same as described in Example 1.

[0030] The obtained CF / PEG is used in practical applications: the CF@LDH / PEG in Example 1 is replaced by CF / PEG, and the other methods are the same as those described in Example 1.

[0031] Example 3: Preparation of CF@LDH / decanoic acid: 4 g PEG in Example 1 was replaced with 4 g decanoic acid, and the rest of the method was the same as described in Example 1.

[0032] The obtained CF@LDH / decanoic acid is used in practical applications: the CF@LDH / PEG in Example 1 is replaced by CF@LDH / decanoic acid, and the other methods are the same as those described in Example 1.

[0033] Example 4: Preparation of CF@LDH / dodecanol: 4 g of PEG in Example 1 was replaced with 4 g of dodecanol, and the rest of the method was the same as described in Example 1.

[0034] The obtained CF@LDH / dodecanol is used in practical applications: the CF@LDH / PEG in Example 1 is replaced by CF@LDH / dodecanol, and the other methods are the same as those described in Example 1.

[0035] Example 5: Preparation of CF@LDH / octadecane: 4 g of PEG in Example 1 was replaced with 4 g of octadecane, and the rest of the method was the same as described in Example 1.

[0036] The obtained CF@LDH / octadecane is used in practical applications: the CF@LDH / PEG in Example 1 is replaced by CF@LDH / octadecane, and the other methods are the same as those described in Example 1.

[0037] 3. Characterization of relevant properties of the novel composite flame-retardant phase change materials obtained in Example 1 and Example 2: 1. SEM images of CF, CF@LDH, CF / PEG and CF@LDH / PEG Figure 2 As shown. Figure 2 (a-a') shows that CF with a porous structure was successfully prepared, but the pore size distribution is uneven and the pore positions are relatively messy. Figure 2 (b-b') shows that MgAl-LDH with a crystal structure can be observed to be successfully grown in situ on the carbon pores of CF. And it will not destroy the porous structure of CF. This porous structure makes CF and CF@LDH have strong adsorption capacity. Figure 2 As shown in (c) and (d), due to the strong adsorption capacity of CF and CF@LDH and the synergistic effect of CNF, PEG is enclosed in a complex space with capillary effect composed of porous structure and fiber structure of CNF. Blocky and flocculent PEG can be clearly observed in the SEM images of both, and CNF nanofibers can also be seen. Figure 2 (e) and (f) clearly show the difference in the element contents of C, O, Mg and Al on the surface of CF / PEG and CF@LDH / PEG. The difference in element contents mainly depends on the presence or absence of MgAl-LDH.

[0038] 2. In order to explore the phase composition and crystallinity of CF@Mg Al-LDH, CF / PEG, and CF@LDH / PEG synthesized by hydrothermal method, the samples were tested by X-ray diffractometer. The XRD patterns of the samples are shown in Figure 3(a) shows. PEG has two main peaks, with peaks at 19.0° and 23.6°, corresponding to the (120) and (032) planes of PEG crystals, respectively, indicating that it has good crystallization ability. The characteristic peaks of Mg Al-LDH synthesized by hydrothermal method are mainly 11.7°, 23.6°, 39.7° and 47.1°, which correspond to the lattice planes of (003), (006), (015) and (018) (PDF#35-0964), corresponding to the special crystal structure of Mg Al-LDH. However, CF@LDH has obvious NaCl characteristic peaks, which may be due to the fact that NaCl with good crystallinity cannot be completely removed despite filtration and centrifugal washing. The diffraction peaks of CF / PEG and CF@LDH / PEG composite materials are a mixture of the peaks of each component, and no new peaks appear, indicating that they are only physically combined and no chemical reaction occurs.

[0039] The chemical structures of CF, PEG, CF@LDH, CF / PEG and CF@LDH / PEG samples were analyzed by Fourier transform infrared spectroscopy (FT-IR). Figure 3 (b) It is worth noting that the infrared absorption spectrum of PEG is at 1340 cm -1 and 2885 cm -1 The absorption peak at -CH 2 - group stretching vibration, while at 1110 cm -1 There is an obvious absorption band at 3440 cm -1 All of them have absorption peaks attributed to -OH. Combining the results of XRD and FT-IR, the composite nanofiber film successfully combines the raw materials used evenly and firmly, and no chemical reaction occurs during the bonding process.

[0040] 3. Figure 4 (a) shows the differential scanning calorimetry (DSC) curves of PEG and composite nanofibers. The melting points and enthalpy values ​​of PEG, CF@LDH, CF / PEG, and CF@LDH / PEG can be obtained by DSC measurement. PEG exhibits an obvious endothermic process, and its melting point (T m ) is 62.7 °C, and the melting enthalpy (ΔH m) is 170.3 J / g, indicating that it is a good energy storage and heat absorption material. It is worth noting that the enthalpy values ​​of CF / PEG and CF@LDH / PEG composites are lower than the phase change enthalpy of pure PEG. This is because the addition of CF and CNF reduces the relative content of pure PEG. In addition, the phase change process of CF / PEG and CF@LDH / PEG is also different from that of pure PEG, and their melting points are lower than those of pure PEG. This may be because the CF / CNF skeleton structure affects the phase change behavior of PEG therein. Although PEG still maintains good crystallinity in CF / PEG and CF@LDH / PEG, the various materials in the composite nanofibers can significantly affect the free movement of PEG molecular chains during heating or cooling.

[0041] Figure 4 (b) shows the 2 Thermogravimetric analysis (TGA) curves of CF, CF@LDH, CF / PEG, and CF@LDH / PEG under N atmosphere. These experiments were performed under N 2 The test was carried out in an environment with a test temperature range of 30-800℃ and a heating rate of 10℃ / min. It can be seen that CF finally suffered only 4% mass loss, which may be caused by the thermal decomposition of the residual NaCl and a very small amount of agar in CF. Since there is a part of bound water in CF@LDH, it begins to lose mass at the beginning of heating. After the temperature reaches 200℃, MgAl-LDH begins to decompose by heat. This process may be relatively slow, so the TGA curve of CF@LDH shows a uniform and slow downward trend. For CF / PEG and CF@LDH / PEG, since the main components of both are PEG, their mass loss areas are mainly concentrated between 300℃-400℃, and PEG decomposes by heat in this temperature range. Based on the test results of thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), it can be seen that the composite membrane has good thermal stability and thermal practicality, and has certain thermal management and energy storage potential.

[0042] 4. If Figure 5 As shown. As mentioned above, the powder was pressed into tablets using the transient plane source method (TPS) at a test temperature of 30°C and the thermal conductivity of the sample was measured in a thermal constant analyzer. The thermal conductivities of PEG, CF / PEG and CF@LDH / PEG were 0.25, 0.43 and 0.44 W / m·K, respectively. Due to the short chain structure of the PEG polymer, the polymer has an inherently low thermal conductivity. The CF porous carbon network with excellent thermal conductivity is uniformly dispersed in the PEG matrix as a skeleton, forming a three-dimensional thermal conductive path in the composite material.

[0043] 5. By evaluating the time-temperature curve and infrared (IR) image of the sample heating process, the actual application performance of the composite film can be intuitively observed, such as Figure 6 As shown. At the beginning of the experiment, the surface temperature of CF / PEG and CF@LDH / PEG was 20℃. As the heating plate was heated to 105℃, the color of the film changed significantly, indicating that the surface temperature of the film increased over time. After heating for 2000 seconds, the sample temperature reached a stable state, and the temperatures of CF / PEG and CF@LDH / PEG were about 72℃ and 79℃. At about 800 seconds to 1800 seconds, CF / PEG and CF@LDH / PEG showed obvious temperature platforms between 50-60℃, indicating that the PEG in the composite film had a phase change. After the phase change was completed, the temperature of the composite film continued to rise rapidly. These results can be explained by two reasons. First, the presence of polyethylene glycol absorbed heat, thereby reducing the temperature. Second, the material has good thermal conductivity, which increases the temperature. Since the phase change enthalpy of CF / PEG and CF@LDH / PEG is basically similar, the reason for the difference in the final stable temperature of CF / PEG and CF@LDH / PEG may be the difference in thermal conductivity between the two, which requires further testing. The experimental results show that the surface temperature of CF / PEG and CF@LDH / PEG is stable and uniform, showing good reliability and stability under repeated and long-term working conditions. In addition, the thermal conductivity test results and DSC test results are consistent with the conclusions of infrared thermal imaging.

[0044] 6. In order to study the photothermal conversion characteristics of the composite film, a photothermal conversion experimental device was established, such as Figure 7 As shown in (a), the device mainly consists of a solar simulation lamp, an insulation layer, a thermocouple and a data collection system.

[0045] The power of the sunlight simulation lamp is basically equivalent to the average solar radiation power of Beijing, China, which is 130mWcm -2 , used to simulate the composite nanofiber samples irradiated by sunlight.

[0046] The main material of the insulation layer is low-cost closed-cell insulation material composed of nitrile rubber, polyvinyl chloride, etc.

[0047] The photothermal conversion performance of composite nanofibers mainly depends on their ability to absorb light. The wavelength range and energy range of sunlight irradiating on the ground are mainly concentrated in the ultraviolet / visible / near-infrared range of 200-800nm. UV-VIS-DRS (Hitachi U4150) is used to measure the absorbance of the sample and pure PEG in the ultraviolet / visible / near-infrared range of 200-800nm. Figure 7The data in (b) show that PEG exhibits weak absorbance in this wavelength range, while CF / PEG and CF@LDH / PEG composite films exhibit strong absorbance in this range, showing strong light absorption capacity.

[0048] according to Figure 7 From the time-temperature evolution curve in (b), it can be seen that the temperature of the pure PEG sample rises slowly, and PEG does not reach the phase transition temperature in the end, while the temperature of the composite film sample quickly reaches a temperature far higher than the phase transition temperature range of PEG. As the irradiation time increases, the inflection point in the temperature curve of the composite film appears in the temperature range of 58℃-62℃, which is consistent with the phase transition temperature of the composite. This indicates that PEG melts when the absorbed energy is converted into heat energy and stored in the composite. After the irradiation of the simulated light stops, the surface temperature of the composite nanofiber membrane drops rapidly to the condensation point of about 50℃. These temperature platforms indicate that the composite nanofiber membrane releases the stored heat energy during the cooling process. In contrast, no melting and cooling platforms are observed in the temperature evolution curve of pure PEG, because the highest temperature of pure PEG under simulated light does not reach the phase transition temperature. These results indicate that photothermal storage is an effective heat transfer achieved by absorbing light energy and transferring heat to the surrounding PEG through the CNT network with high thermal conductivity and strong light absorption ability. The stored heat energy can be released during the cooling process of PEG. Area 8cm 2 The composite film sample was at 130mW / cm 2 Under the sunlight simulation lamp, the corresponding relationship between the light-to-heat conversion efficiency of each sample is: η CF / PEG =72.2%, η CF@LDH / PEG =80.1%.

[0049] 7. The bending and tensile properties of CF@LDH / PEG were simply tested using weights. Figure 8 As shown in (a), due to the presence of cellulose and the film structure, CF@LDH / PEG can maintain a stable shape after multiple bending. Under the action of a 500g weight, the CF@LDH / PEG film does not experience any tensile fatigue. This shows that the flexibility brought by the special structure of CF@LDH / PEG allows it to be wrapped on the surface of different devices and will not be damaged during the coating process.

[0050] 8. Use an adiabatic accelerating calorimeter (ARC) to detect battery thermal runaway.

[0051] Fig. 9The temperature changes of adiabatic accelerated calorimetry experiments of 18650 lithium-ion batteries wrapped and unwrapped by CF@LDH / PEG at 100% SOC are given. During the adiabatic accelerated calorimetry experiment, the sample is first placed in the sample chamber, and then the experimental starting temperature, thermal sensitive temperature, heating rate, termination temperature, safety temperature, heating range and waiting time are set. Start the calorimeter. The calorimeter first works in the "heating" state. After the heater heats the furnace body to the starting temperature through the heater under the set starting heating rate conditions, the system is in the "waiting" mode, and the sample is heated by the constant temperature furnace body. When the sample temperature is consistent with the temperature in the adiabatic furnace, it is in a uniform equilibrium state, and the system automatically enters the "searching" mode; in the "searching" stage, the temperature rise rate of the sample is compared with the set temperature rise rate. For lithium-ion batteries, the self-discharge temperature rise rate is generally 0.02℃ / min. If the detected temperature rise rate is less than this value, it enters the next "heating-waiting-searching" stage. Otherwise, if the sample temperature rise rate is monitored to be greater than this value, it enters the "heat release" mode. As the temperature rise rate gradually increases, the battery gradually enters the thermal runaway stage. At this time, the controller controls the heater to compensate for the temperature in the heating furnace so that the heating furnace and the battery sample maintain a uniform temperature.

[0052] Table 1 shows the exothermic mode start time and start temperature, reaction end time and end temperature, and maximum temperature rise rate of the adiabatic accelerated calorimetry experiment of 18650 lithium-ion batteries wrapped and not wrapped with CF@LDH / PEG at 100% SOC.

[0053] Table 1: Data table of sample CF@LDH / PEG for delaying battery thermal runaway Depend on Fig. 9 As shown in Table 1, the thermal runaway of the 18650 battery wrapped by CF@LDH / PEG has been weakened to a certain extent, the time of thermal runaway has been postponed, and the maximum temperature rise rate has been greatly reduced, indicating that CF@LDH / PEG has a certain delaying effect on the thermal runaway of the battery.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A multifunctional flame-retardant phase change film based on PEG, LDH and CF, characterized in that: Taking CF carbon foam skeleton as the matrix and as the shape skeleton, light-absorbing and thermal conductive material, polyethylene glycol as the phase change material, and adding flame retardant layered double hydroxide LDH for full mixing and hybridization, a multifunctional flame retardant phase change film was obtained by melt laying method; wherein: the mass ratio of phase change material, skeleton and flame retardant is: 7-8:1-1.5:1-1.

5.

2. A multifunctional flame-retardant phase change film based on PEG, LDH and CF according to claim 1, characterized in that: The phase change material is decanoic acid or octadecane replacing polyethylene glycol; the skeleton is polypyrrole tube PPY or carbonized gelatin replacing CF.

3. The method for preparing the multifunctional flame-retardant phase change film based on PEG, LDH and CF according to claim 1, characterized in that: The specific steps are as follows: (1) Preparation of CF skeleton: 0.5 g agar powder and 2 g sodium chloride were dissolved in 20 mL deionized water, and the mixed solution was heated to 90 °C and stirred continuously. The water in the mixed solution was evaporated continuously until the mixed solution formed a uniform hydrosol; after cooling to room temperature, the formed hydrosol was freeze-dried in a -50 °C vacuum freeze dryer for 72 h to obtain a white solid product; the white solid product was placed in a tubular furnace, and the heating rate was controlled to be 10 °C / min under an argon atmosphere, and the temperature was raised to 700 °C and heated for 2 h; after cooling to room temperature, the product was immersed in water overnight to dissolve NaCl, and then filtered and washed, and the filter cake was dried at 80 °C to obtain a nanoporous carbon foam CF; (2) Preparation of CF@Mg Al-LDH composite material: 0.5 g of CF powder, 1.62 g of MgCl2·6H2O, 0.9 g of AlCl3·H2O and 2.4 g of urea were weighed and placed in a high-pressure reactor. After mixing evenly, the reactor was placed in an oven at 100°C for hydrothermal reaction for 12 h. After cooling to room temperature, the product was taken out and centrifuged and washed three times, and then dried at 80°C to obtain CF@MgAl-LDH. (3) Preparation of composite membrane: Weigh 0.5 g CF@MgAl-LDH powder, 25 g cellulose, and 4 g PEG and mix them in 100 ml deionized water. Stir at 600 r / min for 6 h to obtain a uniform mixture. Pour the mixture into a cylindrical mold with a radius of 15 mm and a height of 20 mm. Place the mold in a vacuum oven at 80 °C and bake for 24 h. In other words, the CF@LDH / PEG film is obtained by the melt casting method.

4. The preparation method according to claim 3, characterized in that: The multifunctional flame-retardant phase-change film is solid powder or block.

5. Application of the multifunctional flame-retardant phase-change film based on PEG, LDH and CF according to claim 1 or the multifunctional flame-retardant phase-change film based on PEG, LDH and CF prepared by the method according to claim 3 in delaying thermal runaway of batteries, characterized in that: The composite film is coated on the battery and placed in the insulated cavity of an adiabatic accelerating calorimeter. The temperature change is monitored by a thermocouple temperature measuring device, and the real-time temperature, temperature difference and maximum temperature rise rate under different working environments are obtained to characterize the thermal runaway delay performance. The composite nanofibers are placed under a sunlight simulation lamp for irradiation, and their temperature changes are monitored. The photothermal conversion capacity and thermal runaway condition are determined based on the real-time temperature, sample specific heat and light power within a certain period of time.

6. The use according to claim 5, characterized in that: The packaging material of the battery is any one of aluminum alloy, copper or iron, and the heat sink is foamed nickel or foamed copper or any metal.

7. Application of the multifunctional flame-retardant phase-change film based on PEG, LDH and CF according to claim 1 or the multifunctional flame-retardant phase-change film based on PEG, LDH and CF prepared by the method according to claim 3 in photothermal energy storage materials, microelectronic packaging materials or intelligent building materials.

Citation Information

Patent Citations

  • High-adsorption and ultra-light carbon aerogel material with three-dimensional graded pore structure for water treatment and preparation method of high-adsorption and ultra-light carbon aerogel material

    CN107552023A

  • Lightweight flexible carbon foam-based phase change composite material and preparation method thereof

    CN110184035A

  • Composite phase-change flame-retardant material with thermal management performance and electromagnetic shielding function as well as preparation method and application of composite phase-change flame-retardant material

    CN115322797A

  • Flame-retardant phase change film based on PEG and MWCNT-COOH combined electrostatic self-assembly method and preparation method and application thereof

    CN117946434A

  • Heat storage composition

    WO2021241432A1

Cited By

  • Phase change material intercalated hydrotalcite modified asphalt and preparation method thereof

    CN120290008A